Identification of ZmSNAC06, a Maize NAC Family Transcription Factor with Multiple Transcripts Conferring Drought Tolerance in Arabidopsis - Fei Wang; Yong Chen; Ruisi Yang; Ping Luo; Houwen Wang; Runze Zhang; Wenzhe Li; Ke Yang; Xinlong Xu; Zhuanfang Hao; Xinhai Li (Plants)
Drought is one of the most serious environmental stresses affecting crop production. NAC transcription factors play a crucial role in responding to various abiotic stresses in plants. Here, we identified a maize NAC transcription factor, ZmSNAC06, between drought-tolerant and drought-sensitive inbred lines through RNA-seq analysis and characterized its function in Arabidopsis. ZmSNAC06 had five transcripts, of which ZmSNAC06-T02 had a typical NAC domain, while ZmSNAC06-P02 was localized in the nucleus of maize protoplasts and had transactivation activity in yeasts. The expression of ZmSNAC06 in maize was induced by drought. The overexpression of ZmSNAC06-T02 in Arabidopsis resulted in hypersensitivity to abscisic acid (ABA) at the germination stage, and overexpression lines exhibited higher survival rates and higher antioxidant enzyme activities compared with the wild-type under drought stress. These results suggest that ZmSNAC06 acts as a positive regulator in drought tolerance and may be used to improve drought tolerance in crops.